STRENGTH CHECK OF AIR CONDITIONER PANEL MECHANISM BASED ON FINITE ELEMENT MOTHOD - OUYANG Hui; LI DePeng; GAO WenLi; ZOU JinWei (Jixie qiangdu)
The virtual prototyping technology and the finite element analysis method were used to simulate the motion mechanism of a type of air conditioner panel in order to reduce the possibility of the mechanism failure at the design stage. First,the motion of air conditioner panel is analyzed by ADAMS software and load is exported. The results show that the overall motion of the panel is stable,but a large speed change occurs when the panel is fully open. The maximum load appears in the process of air conditioning start-up. Second,the software ABAQUS was used to analyze the stress. It is indicated that the maximum stress region is the contact position between the gear and the rack when the air conditioning starts up. The maximum stress area is the contact position for rack and pinion when the panel is fully open. In both cases,the maximum stress values satisfy the strength requirements. Finally,the simulation analysis is verified by experimental results of Lab VIEW platform.